PENGARUH KUALITAS PRODUK, GAYA HIDUP SEHAT, DAN ACUAN KELOMPOK TERHADAP KEPUTUSAN PEMBELIAN BUAH DI SUPERINDO CABANG SOLO BARU - Aprian Aditama, Rizky Ramadhan; Larasati, Nike (ITB AAS Indonesia Surakarta, 2023)
This study aims to determine the extent to which Product Quality (X1), Healthy Lifestyle (X2), and Group Reference (X3) influence Purchasing Decision (Y). This study uses a quantitative approach with sampling using the Non Probability Sampling method. The type of data used in this study is primary data obtained from questionnaires filled out directly by respondents. Secondary data comes from books, journals, research results, practical work reports and related to the author's research object. In this study, the population that will be taken is all consumers of Superindo branch Solo Baru, which is immeasurable. Sample measurement uses the formula proposed by Hair et al., (2010) which is 115 respondents. The analysis tool used is multiple linear regression analysis. Using the SPSS analysis tool, the results of the study show that Product Quality (X1), Healthy Lifestyle (X2), and Group Reference (X3) simultaneously influence Purchasing Decision (Y). Keywords : Product Quality, Healthy Lifestyle, and Group Reference, Purchasing Decision.